Is the bowshock of the runaway massive star HD 195592 a Fermi source? - De Becker, Michael (2013)
Context. HD 195592 is an O-type super-giant star, known as a well-established runaway. Recently, a Fermi gamma-ray source (2FGL J2030.7+4417) with a position compatible with that of HD 195592 has been reported. Aims: Our goal is to explore the scenario where HD 195592 is the counterpart of the Fermi gamma-ray source, modeling the non-thermal emission produced in the bowshock of the runaway star. Methods: We calculated the spectral energy distribution of the radiation produced in the bowshock of HD 195592 and we compared it with Fermi observations of the 2FGL J2030.7+4417. Results: We present relativistic particle losses and the resulting radiation of the bowshock of HD 195592 and show that the latter is compatible with the detected gamma-ray emission. Conclusions: We conclude that the Fermi source 2FGL J2030.7+4417 might be produced, under some energetic assumptions, by inverse Compton up-scattering of photons from the heated dust in the bowshock of the runaway star. Therefore, HD 195592 might be the very first object detected belonging to the category of gamma-ray emitting runaway massive stars, whose existence has been recently predicted.